2017
DOI: 10.1007/s00280-017-3423-5
|View full text |Cite
|
Sign up to set email alerts
|

Superactive human leptin antagonist (SHLA), triple Lan1 and quadruple Lan2 leptin mutein as a promising treatment for human folliculoma

Abstract: PurposeThere are no data showing a direct correlation between obesity and increased blood leptin levels with folliculoma. Moreover, folliculoma is not the best studied among other ovarian cancer types. We investigated whether oestradiol can modulate ObR expression in some oestrogen-responsive tissues and that leptin exerts its activity not only via the leptin receptor but also through cross talk with other signalling systems. We hypothesise that blocking ObR expression could be a novel treatment for gonadal ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The analysis also showed that leptin promotes cell cycle progression, as demonstrated by an increased cell population in both the S and G2/M phases [38]. Other studies confirmed twofold higher leptin receptor gene and protein expression in both epithelial ovarian cancer and cancer granulosa cell lines compared to non-cancer cell lines, which is associated with poor treatment prognosis [39, 40]. In addition leptin has also been shown to stimulate the migration and invasion of ovarian cancer cells, regardless of the degree of leptin receptor expression in the cells [36, 37].…”
Section: The Influence Of Leptin On the Development Of Ovarian Cancermentioning
confidence: 99%
“…The analysis also showed that leptin promotes cell cycle progression, as demonstrated by an increased cell population in both the S and G2/M phases [38]. Other studies confirmed twofold higher leptin receptor gene and protein expression in both epithelial ovarian cancer and cancer granulosa cell lines compared to non-cancer cell lines, which is associated with poor treatment prognosis [39, 40]. In addition leptin has also been shown to stimulate the migration and invasion of ovarian cancer cells, regardless of the degree of leptin receptor expression in the cells [36, 37].…”
Section: The Influence Of Leptin On the Development Of Ovarian Cancermentioning
confidence: 99%
“…Whether leptin might regulate angiogenesis in HCC through these pathways requires further confirmation. Several groups have developed compounds or antibodies targeting leptin/Ob-R signaling that show significant anticancer effects in vitro or in vivo , but have not been applied clinically 64 , 65 .…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…In our previously published data, we demonstrated that the negative effect of leptin on the proliferation of several epithelial and folliculoma ovarian cancer cells can be partially or completely reversed by leptin receptor antagonist treatment via interactions with cell cycle protein expression (12,13). A number of leptin receptor antagonists have been synthesised for therapeutic use, with several completing preclinical testing (19) indicating their possible use in anticancer therapy.…”
mentioning
confidence: 98%
“…Obesity is a risk factor for several different types of cancer, significantly promoting cancer incidence, progression, poor prognosis and resistance to anti-cancer therapies. The increased risk of ovarian cancer, both epithelial and folliculoma, are correlated with obesity; elevated leptin secretion and higher leptin receptor expression has been described in ovarian cancer versus non-cancer cells (12,13). Although data pointing to the relationship between HDAC and leptin are scarce, it has been reported that HDAC5 expression is regulated by dietary lipids and leptin and hypothalamic HDAC5 is an important component of leptin signalling (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation